Water policy - water politics: Social engineering and strategic action in water sector reform - Peter P. Mollinga (University of Bonn, Center for Development Research (ZEF), 2007)
The objective of this paper is to map the 'politics of water' as a field of research. Such mapping logically has two parts. The first is an explanation of what is meant by politics and what could be the overall conceptual approach for analysing the politics of water - the formal part of the mapping. The second part of the mapping is the substantive dimension: what are the concrete issues and questions around which research on water politics could be organised? While the first part can have a single answer, the approach one prefers to take, the second is an in principle endless list of relevant and interesting topics for concrete investigation, each with their own specific conceptual and methodological demands. Selection within that list follows primarily, at least in this paper, from an assessment of what are pertinent policy questions in (a certain part of) the real world of water resources management. This paper focuses on the issue of water sector reform in developing and transition countries, particularly the reform of the public organisations that manage agricultural water. Agriculture is the dominant form of water use in most developing and transition countries, and changes in water resources management towards a more 'integrated' approach require quite fundamental changes in how agricultural water management is done. The need for a more integrated approach to water resources management is taken as the context for the argumentation in this paper, though 'integration' is by no means a clear, single 'thing', but a contested concept.
urn:nbn:de:0202-20080911190
Keywords: 330